Payment integrity in government programs: Takeaways from incorporating the behavioral sciences in US federal evaluations - Maya Duru; Hanna Hoover; Heather Barry Kappes; David Schwegman; Brigitte Seim; Mattie Toma; Mary Clair Turner (Proceedings of the National Academy of Sciences, 2026)
A primary way the US federal government delivers public goods and services is via monetary payments. Ensuring that these payments are calculated accurately, delivered on time, and made to the correct recipients is important for government fiscal health. Inaccurate or delayed payments can weaken public trust in the government and undermine government accountability. In this article, we examine findings from a set of impact evaluations assessing interventions designed to improve payment integrity in US federal programs. The low-cost, evidence-based interventions draw on insights from the social and behavioral sciences and include modification of forms, changes to how and when agencies request information, and altering existing communications. The evaluations were conducted by the US General Services Administration’s Office of Evaluation Sciences in collaboration with agency partners. We extract three takeaways across four representative evaluations. First, the real-world evaluations validate a key implication of the behavioral science literature: interventions that reduce burdens for individuals have small effects that meaningfully improve payment integrity at scale. Second, effects attenuate across interventions and over time, suggesting a need for iterative evaluation. Finally, bureaucratic hurdles and administrative complexity are the main barriers to translating academic insights into real-world government programs. Addressing these challenges will require close collaboration between behavioral scientists and practitioners throughout the intervention design and evaluation process.